The Relationship between House Conditions and the Household Contacts with the Incidence of Children's Pulmonary Tuberculosis - Nasution, Rizqiani Astrid; Wardani, Dyah Wulan Sumekar Rengganis; Pramesona, Bayu Anggileo; Saputra, Oktadoni (Poltekkes Kemenkes Tanjung Karang, 2024)
Tuberculosis (TB) is a high risk in vulnerable groups with low immunity, such as children. Environmental factors and household contacts influence the high incidence of tuberculosis. This study aimed to analyze the relationship between housing conditions and the presence of household contacts with the incidence of pulmonary tuberculosis in children. This study used a case-control design. This study used a case-control design at the Puskesmas Kedaton Bandar Lampung from December 2023 to January 2024. The total sample was 58 children (29 cases and 29 controls), selected using Simple Random Sampling. The variables of this study were residential density, humidity, lighting, floor type, ventilation area, and the presence of household contacts. This study used univariate analysis, bivariate analysis with chi-square, and multivariate with multiple logistic regression. This study shows that there is a relationship between lighting (p=0,008), ventilation area (p=0,032), and the presence of household contacts (p<0,001) with the incidence of pulmonary TB in children. The factor most associated with the incidence of pulmonary TB in children was lighting (OR=6.061; 95% CI=1.768-20.777), which means children with home lighting that does not meet the requirements have a 6.061 times higher risk of experiencing childhood pulmonary TB than those who meet the lighting requirements. There is a relationship between lighting, ventilation area, and the presence of household contacts with the incidence of pediatric pulmonary tuberculosis in the Puskesmas Kedaton, Bandar Lampung working area.